(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article explores the intricate relationship between leadership and management psychology, highlighting their mutual influence and practical application in organizational settings. The study focuses on essential leadership qualities such as emotional intelligence, decision-making skills, and adaptability, which are crucial in fostering productive team dynamics. It further examines the psychological principles underlying group behavior and motivation, offering insights into how effective leadership can enhance performance, cooperation, and morale within teams. Additionally, the article presents various modern management methods that align with psychological approaches to improve efficiency and organizational success. The integration of psychological understanding into leadership practices is emphasized as a key factor in developing resilient and goal-oriented teams.